2014
DOI: 10.4209/aaqr.2013.04.0135
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Evaluation of Prepared Fe2O3/Al2O3 Oxygen Carriers for Chemical Looping Process

Abstract: Alumina supported Fe 2 O 3 was prepared to evaluate its feasibility as an oxygen carrier for chemical looping using a thermogravimetric analyzer (TGA) and fixed bed reactor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 28 publications
1
31
0
Order By: Relevance
“…In our previous study, nickel ferrite (NiFe 2 O 4 ) powder with a single spinel phase demonstrated higher redox behaviour than standard nickel oxide (NiO) and iron oxide (Fe 2 O 3 ) by a thermogravimetric analyzer (TGA). However, the agglomeration phenomenon of reduced state of prepared oxygen carriers with a low thermal stability under high reaction temperature is considered to be the main concerns to degrade their multi-redox cycling behaviour in the CLC process (Lambert et al, 2011;Kuo et al, 2013;Chiu et al, 2014;Tseng et al, 2014). The addition of Al 2 O 3 as inert support in NiFe 2 O 4 system was preliminary investigated, while the formation of new spinel phase of nickel aluminium ferrite (NiFeAlO 4 ) was obtained.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, nickel ferrite (NiFe 2 O 4 ) powder with a single spinel phase demonstrated higher redox behaviour than standard nickel oxide (NiO) and iron oxide (Fe 2 O 3 ) by a thermogravimetric analyzer (TGA). However, the agglomeration phenomenon of reduced state of prepared oxygen carriers with a low thermal stability under high reaction temperature is considered to be the main concerns to degrade their multi-redox cycling behaviour in the CLC process (Lambert et al, 2011;Kuo et al, 2013;Chiu et al, 2014;Tseng et al, 2014). The addition of Al 2 O 3 as inert support in NiFe 2 O 4 system was preliminary investigated, while the formation of new spinel phase of nickel aluminium ferrite (NiFeAlO 4 ) was obtained.…”
Section: Introductionmentioning
confidence: 99%
“…oxygen carriers were examined by a field emission scanning electron microscope (FESEM) have been clearly described in previous publication. (Chiu et al, 2014) …”
Section: Introductionmentioning
confidence: 99%
“…11, the reduction conversion for experiments conducted with FeAl320-S10 pellets was decreased from about 90% to 70% after operated for 20 redox cycles, indicating that the recyclability of Fe 2 O 3 was considerably improved with Al 2 O 3 support. Chiu et al (2014) indicated that the conversion of Fe 2 O 3 pellet was decayed rapidly after the second redox cycle. However, the conversion of Fe 2 O 3 /Al 2 O 3 pellet was maintained at above 70% during continuous redox cycling.…”
Section: Resultsmentioning
confidence: 99%
“…Insignificant deactivation, agglomeration, carbon deposition, and attrition were observed by Abad et al (2007) using the Al 2 O 3 -supported Fe 2 O 3 oxygen-carriers for natural gas or syngas combustion in a thermogravimetric analyzer. Chiu et al (2014) reported that Fe 2 O 3 /Al 2 O 3 oxygen carriers demonstrated reasonable oxygen conversion and delivered high CO 2 yields for chemical looping combustion of methane and syngas (CO/H 2 ) in a fixed bed reactor. Ku et al (2014) revealed that the completely methane combustion was achieved for experiments carrier out with Fe 2 O 3 /Al 2 O 3 in a moving bed fuel reactor, and carbon deposition was significantly reduced.…”
Section: Introductionmentioning
confidence: 99%